Attention and acute judo-specific effort in athletes preparing for Olympic competition - Sterkowicz-Przybycien, K.; Blecharz, J.; Sterkowicz, S.; Luzczynska, A. (Archives of Budo, 2015)
Study Aim: The study investigated the changes in attention concentration corresponding to body activation in judoists of different competitive levels. The changes in attention processes were tested in the context of judo-specific effort. Material and Methods: The Special Judo Fitness Test (SJFT) was administrated to 23 elite judoists during their preparation for the Olympic Games, London 2012. The attention processes were measured with d2 test before the fitness test and repeated immediately after the SJFT. Results: Compared to pretest, the results obtained after the SJFT indicated that the processing speed and the concentration performance increased and the percentage of errors dropped. Participants ranked higher on the International Judo Federation ranking obtained better results than judoists of the national level. The percentage of errors in the d2 test was unsatisfactory in the both international and national groups: the high speed of processing was accompanied by a low quality of performance. Conclusions: High processing speed was associated with performance of low quality, which might be improved in the course of psychological and tactical training. Coaches may use attention tests to monitor athletes' psychophysiolgoical states and facilitate performance.